Diagnostic Utility of AMCAR and p63 Cocktail Antibody in the Benign and Malignant Lesions of Prostate - Chougani, Sujitha; V, Sunandalakshmi G; Kharidehal, Durga; V, Ravi Sankar; Vissa, Santhi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Histopathological examination of prostatic specimen is gold standard for the diagnosis of prostate cancer. Current study evaluates the expression of AMACR and p63 in the prostate lesions using AMACR and p63 cocktail. Materials and Method: Total of 180 cases were collected and Haematoxylin and Eosin staining performed followed by immunohistochemical analysis using AMACR and p63 antibody. Result: Out of 180 cases, Benign Prostatic Hyperplasia is the most common lesion noted in about 120 cases. In this study, the predominant population was in the 6th to 7th decade of age. Most of the patients presented with difficulty in micturition. Immunohistochemistry revealed that p63 expression is positive in all normal basal cells, 118 cases (98.33%) were negative for AMACR and only 2 cases were showing focal and weak AMACR immunoreactivity. AMACR was positive in all the 6 HGPIN cases with variable intensity. Out of 5 LGPIN cases AMACR was positive in 3 cases with low intensity, remaining 2 cases shows AMACR negative. p63 is positive in all 11 PIN cases (LGPIN & HGPIN) showing discontinuous staining pattern. All 22 cases of Prostatic adenocarcinomas were negative for p63 and all cases expressed positive immunostaining with AMACR. A diagnosis of adenocarcinoma was made in 48% of atypical cases. Cases which were negative for both AMACR and p63 were diagnosed as Atypical Small Acinar Proliferation, for which further follow-up is required. Conclusion: AMACR/p63 Cocktail antibody is very much useful as it saves time, tissue and is cost-effective.